2021
DOI: 10.1038/s41598-021-91086-6
|View full text |Cite
|
Sign up to set email alerts
|

Native mass spectrometry analyses of chaperonin complex TRiC/CCT reveal subunit N-terminal processing and re-association patterns

Abstract: The eukaryotic chaperonin TRiC/CCT is a large ATP-dependent complex essential for cellular protein folding. Its subunit arrangement into two stacked eight-membered hetero-oligomeric rings is conserved from yeast to man. A recent breakthrough enables production of functional human TRiC (hTRiC) from insect cells. Here, we apply a suite of mass spectrometry techniques to characterize recombinant hTRiC. We find all subunits CCT1-8 are N-terminally processed by combinations of methionine excision and acetylation ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 70 publications
0
7
0
Order By: Relevance
“…22 CCT5 can form dimers with all eight subunits except for CCT8, indirectly supporting this viewpoint. 24 The processes of TRiC/CCT disassembly and degradation are less well understood than those of its assembly. Early studies demonstrated that two octameric rings disassemble one ring at the same time to generate microcom-plexes and monomers, not double rings.…”
Section: Architecture and Overall Structure Of Tric/cctmentioning
confidence: 99%
“…22 CCT5 can form dimers with all eight subunits except for CCT8, indirectly supporting this viewpoint. 24 The processes of TRiC/CCT disassembly and degradation are less well understood than those of its assembly. Early studies demonstrated that two octameric rings disassemble one ring at the same time to generate microcom-plexes and monomers, not double rings.…”
Section: Architecture and Overall Structure Of Tric/cctmentioning
confidence: 99%
“…TRiC/CCT consists of two stacked anti-parallel rings of eight hetero-oligomers and forms a hexadecamer. Each subunit possesses its own function and CCT5 is thought to play a master role in assembly and disassembly of the complex 48 .…”
Section: The Regulatory Interaction Of Hsf1 With Chaperones or Chaper...mentioning
confidence: 99%
“…This idea is supported by mass spectrometry analysis of human CCT purified from insect cells, in which CCT5 was the most stable subunit observed under chemical destabilization conditions, hence, the most likely to self-assemble or co-assemble with other subunits. Importantly, CCT5 formed dimers with all subunits except for CCT8 ( Collier et al, 2021 ). However, since CCT subunits are independently transcribed in the crowded cellular environment, bringing together all the subunits for assembly could be challenging.…”
Section: Introductionmentioning
confidence: 99%
“…N-terminal modifications may also affect the formation of the CCT complex since the N-termini of subunit apical domains mediate inter-ring cooperativity. Truncation of N-termini through methionine loss or acetylation could lead to degradation of CCT subunits ( Collier et al, 2021 ). Evident from these experiments is that assembly/disassembly of the CCT complex may be linked to the monomer/oligomer pool in a dynamic process that ultimately controls protein folding activity and critical cell functions.…”
Section: Introductionmentioning
confidence: 99%